Evaluación de biopolímero a partir de cáscara de plátano para la remoción de sólidos suspendidos en aguas residuales domésticas - Intriago Barberán, Lauro Antonio (2024)
The objective of this research was to evaluate the efficiency of male banana peel (Musa paradisiaca L.) in removing turbidity in wastewater from the Calceta treatment plant. This experimental research was developed in three phases: the first phase consisted of the physical and chemical characterization of domestic wastewater in order to identify its properties. Subsequently, the next phase was about the efficiency of the bioflocculant in the removal of suspended solids. For this, a dissolution of the tannins contained in 50 g of raw material in 1L of distilled water was carried out. An experimental design was designed out with 9 treatments and 3 repetitions each one in a volume of 500 ml of waste water. The third phase was focused on estimating the +economic viability of the treatment with better experimental results based on conventional treatments. As such, it is evident that the treatment that showed the best results in the removal of total suspended solids and turbidity was T1 in which 30 ml of male banana peel flocculant with pH 4 was used, achieving a removal compared to the initial values of the 97.24% for TSS and 59.86% for turbidity; showing the statistical difference with the other treatments. In this way, the alternative hypothesis proposed is accepted: The application of bioflocculants based on banana peels achieves a high percentage of removal of suspended solids in wastewater treatment.